Evaluation of Penalty Corner Success Rates for Indoor Hockey Players - Hambali, Sumbara; Muharam, Deni; Gunawan, Gugun; Hardi, Veny Juniarni (Indonesian Journal of Physical Education and Sport Science, 2024)
Study purpose. Penalty corner is a situation that can be used as an opportunity to increase the score in indoor hockey. However, sometimes players cannot take advantage of this situation, so the opportunity to score a goal is lost. One of the reasons is that coaches pay very little attention to penalty corner training, so they don't have data about the abilities of their players. The aim of this research is to determine the success rate of penalty corners for STKIP Pasundan Cimahi indoor hockey players. Materials and methods. The research method used is a quantitative descriptive research method with a survey approach. The research subjects involved were indoor hockey athletes who were members of the STKIP Pasundan indoor hockey team who competed in the National Championship at Jakarta State University in May 2023, totaling 11 men. For the research instrument, the penalty corner test was used, which researchers analyzed starting from feeder-stopper-shooter and also success in putting the ball into the goal. The analysis uses a percentage approach, to see how successful the athletes are in taking penalty corners, and also what category they fall into. Results. The results of research conducted on evaluating the success rate of penalty corners for STKIP Pasundan indoor hockey players were good, based on consideration of the highest frequency in the above average category amounting to 6 people or 54.5%, high amounting to 2 people or 18.2% and in the average category 3 people or 27.3%. Conclusions. Based on the research results obtained in data analysis, it can be concluded that the success rate of penalty corners for STKIP Pasundan room hockey players is included in the good category. It is hoped that the results of this research will open up insight for hockey coaches in evaluating their palyers' penalty corners.